Small Enterprises' Access to Formal Financial Services: A Review and Assessment - Mario B. Lamberte (Philippine Institute for Development Studies (PIDS), 1995)
Regardless of the growth and rehabilitation of several financial institutions in the last decade, a large number of borrowers have not yet been served, specifically small farm and entrepreneurs. This paper describes the Philippine banking system focusing on its effect to the different socio-economic sectors of the Philippine society. In addition, it examines the supply of financial services provided by the formal financial system and the banking and credit policies of the government.
Keywords: 330; savings mobilization; nonbank financial institutions; financial sector; financial system; banking system; commercial banks; density ratio; thrift banks; rural banks; small and medium enterprises (SMEs)